Assessing the impact of incomplete information on the resilience of financial networks - Cinelli, Matteo; Ferraro, Giovanna; Iovanella, Antonio; Rotundo, Giulia (Annals of operations research, 2021)
This paper explores the issue of robustness against failure cascades for the network of interbank exposures. The available data were retrieved through the Bank for International Settlements database and report only incomplete information from which networks displaying a core-periphery structure were produced. A model of financial contagion was set up to estimate the width and length of the cascades, and was run on the networks detected from the data, as well as simulated data. The role of incomplete information was taken into account by considering a worst-case scenario in which unobserved links were assumed to be present. Given the core-periphery structure of the network, the worst-case scenario was studied in different sub-cases in which different periphery organisations were considered. Simulations showed that the actual network was far from the worst scenario for the propagation of contagion, meaning that the role of unobserved links can substantially alter the resilience of the whole network.